FULL MAGAZINE OF SCIENCE NATURE, VOL. 1(1), DECEMBER 2018 - science nature (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2018)
This file contains the whole published papers in SCIENCE NATURE VOLUME 1, ISSUE 1, dated on 13rd December 2018.